Evaluating E-Procurement Impact In The Public Sector - Boafo, Nana Danso; Ahudey, Eric; Darteh, Andrews Ohene (Archives of Business Research, 2020)
Despite the several benefits gained as a result of e-procurement, the actual potential of it in the public sector in Ghana has not been realized. Studies has further suggested that little is known of e-procurement in most organizations. This demonstrates that the area is under-researched and hence, there is a gap that needs to be filled in literature on the aspect of e-procurement and its impacts in the public sector in Ghana. Therefore the study was to assess the impact of e-procurement in the Ghanaian public sector. The research design was descriptive. Both primary and secondary data was used. Purposive sample method was used to select 15 public sector organisations in Ghana for the study. Multiple linear regression was used to analyze the data. Findings revealed that, e-procurement leads to an effective E-tender evaluation (ETE), improves transparency in supply selection, improve procurement record management and effective supply relationships can be made easy. Based on the finding the study recommended that, Developing countries governments must invest heavily in e-procurement infrastructure to enable its usage in all sectors. And also procurement officers must also be trained well to enable its usage. And lastly e- procurement should be mandatory in all public sector procurements in the country.